Emergence of Aspergillus fumigatus azole resistance in azole‐naïve patients with chronic obstructive pulmonary disease and their homes. (20th November 2017) - Dauchy, C.; Bautin, N.; Nseir, S.; Reboux, G.; Wintjens, R.; Le Rouzic, O.; Sendid, B.; Viscogliosi, E.; Le Pape, P.; Arendrup, M. C.; Gosset, P.; Fry, S.; et al.
Abstract: Azole‐resistant Aspergillus fumigatus (ARAF) has been reported in patients with chronic obstructive pulmonary disease (COPD) but has not been specifically assessed so far. Here, we evaluated ARAF prevalence in azole‐naïve COPD patients and their homes, and assessed whether CYP51A mutations were similar in clinical and environmental reservoirs. Sixty respiratory samples from 41 COPD patients with acute exacerbation and environmental samples from 36 of these patient's homes were prospectively collected. A. fumigatus was detected in respiratory samples from 11 of 41 patients (27%) and in 15 of 36 domiciles (42%). Cyp51A sequencing and selection on itraconazole medium of clinical (n = 68) and environmental (n = 48) isolates yielded ARAF detection in 1 of 11 A. fumigatus colonized patients with COPD (9%) and 2 of 15 A. fumigatus ‐positive patient's homes (13%). The clinical isolate had no CYP51A mutation. Two environmental isolates from two patients harbored TR34 /L98H mutation, and one had an H285Y mutation. Coexistence of different cyp51A genotypes and/or azole resistance profiles was detected in 3 of 8 respiratory and 2 of 10 environmental samples with more than one isolate, confirming the need for a systematic screening of all clinically relevant isolates. The high prevalence of ARAF in patients with COPD and their homes supports the need for further studies to assess the prevalence of azole resistance in patients with Aspergillus diseases in Northern France.